Insect community structure in young and productive coffee farms under leucaena shade of Jember Regency, East Java, Indonesia - Tsaniyah Indah, Zainatuts; Suci Rahayu, Dwi; Setiawan, Rendy (Indonesian Coffee and Cocoa Research Institute, 2024)
The developmental phase of Robusta coffee plantations with agroforestry systems exhibits varying ecosystem characteristics (biotic and abiotic), therebyinfluencing the dynamics of insect community composition within them. One of the major coffee-producing centers in East Java is Jember Regency, where coffeecultivation commonly employs agroforestry systems with various shade trees. Understanding the abundance of insect species in agroforestry coffee plantations is important for determining insect pest control measures. This research aims to study the insect community structure in young coffee and productive coffee farms. Insect sampling was conducted in young coffee farms and productive coffee farms at the Kaliwining Experimental Station, Indonesian Coffee and Cocoa Research Institute (ICCRI), by using road sampling methods with insect nets and pitfall traps. Both types of plantations utilize Leucaena sp. var L2 as shade trees, forming agroforestry coffee plantation systems. Data analysis was performed by calculating the Shannon-Wiener diversity index (H’) to assess insectdiversity and the independent sample t-test to determine differences in insect abundance based on functional roles between the two farms. The results indicatethat the composition and abundance of insects in productive coffee farms are higher than in young coffee farms, resulting in a higher insect diversity index valuefor productive coffee farms (categorized as high), while young coffee farms fall into the moderate category. Furthermore, based on their functional roles, productive coffee farms positively influence the abundance of herbivorous, predatory, parasitoid, and detritivorous insects.